Retention and job satisfaction: a study of career and technical education teachers in Midwestern state - Omar, Muhd Khaizer; Self, Mary Jo; Cole, Ki Lynn Matlock (Human Resource Management Academic Research Society, 2017)
The progressive interests in retaining teachers has long been studied in numerous educational settings. Extensive research pointed out the essential factors towards retaining teachers and understand their job satisfaction to ensure the quality of education is served. Unfortunately, far too little attention has been paid to research pertaining Career and Technical Education (CTE) teachers’ job satisfaction and retention. The role of CTE teachers in preparing skilled-and semiskilled workers for employment is significant. This study focused on factors that affect whether or not CTE teachers stay in the teaching profession by using an online survey. From a population of 2607 teachers with valid email addresses, the total number of completed surveys was 581 participants. A two-phase of multiple linear regression was carried out. Five factors were found to be significant with the teachers’ retention plan: salary, administrative workloads, teachers’ evaluation, and assessment, motivation, and job satisfaction. A chi-square test was employed and showed significant relationships between the teachers’ age when entering the profession and their satisfaction with teaching. The findings contribute implications for educational stakeholders in strategizing plan and action to retain CTE teachers in the CTE school system. To ensure CTE teachers, not only strive and survive in the teaching profession, understand their job satisfaction and reasons for them to remain in teaching is the essence of longevity of CTE school system in the educational paradigm.